Phthalocyanine-based functional polymeric materials : design, synthesis, and applications - Jiang, Jianzhuang; Wang, Hailong; Wang, Kang (Wiley-VCH, 2025)
A carefully curated collection of resources covering the concepts, perspectives, and applications of phthalocyanine chemistry In Phthalocyanine-Based Functional Polymeric Materials: Design, Synthesis, and Applications, a team of distinguished researchers delivers a comprehensive discussion of phthalocyanine-involving hybrids, molecular cages, coordination polymers, covalent organic frameworks, and organic polymers. The book also explains a diverse array of the applications of these novel materials in chemical sensors, organic catalysts, electrocatalysis, photocatalysis, energy storage, and more. The authors have included material designed to help you improve the design of monomers to synthesize polymers with desired functionalities. A valuable reference in the development of phthalocyanine chemistry, readers will also find: A thorough introduction to phthalocyanine-based polymers and their uses in sensors, catalysis, energy storage, and other applications Comprehensive explorations of the extended molecular systems of phthalocyanines, filling the gap between monomeric phthalocyanine compounds and polymers Practical discussions of a variety of phthalocyanine-based polymer systems, their potential applications, and major design and synthesis challenges Complete treatments of these novel materials appropriate for readers in academia and industry Perfect for polymer, organic, inorganic, catalytic, complex, and structural chemists, Phthalocyanine-Based Functional Polymeric Materials will also benefit materials scientists and chemists working in industry.
Keywords: Polymers.; Phthalocyanines.; elektronické knihy; electronic books